2016
DOI: 10.1007/s12687-016-0267-3
|View full text |Cite
|
Sign up to set email alerts
|

Community engagement to inform the development of a sickle cell counselor training and certification program in Ghana

Abstract: Sickle cell disease (SCD) and sickle cell trait (SCT) are highly prevalent in Africa. Despite public health implications, there is limited understanding of community issues for implementing newborn screening and appropriate family counseling. We conducted a 3-day workshop in Kumasi, Ghana, with community leaders as lay program development advisors to assist the development and implementation of a Sickle Cell Counselor Training and Certification Program. We employed qualitative methods to understand cultural, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…They expressed that public education will go a long way to ameliorating public discourses around SCD as a curse or punishment and allow for conventional medical management of SCD while allowing individuals to practice their faith to cope with the complications of the disease. Previous researchers have cited the importance of embedding SCD public health and health education interventions within faith‐based communities (Anie et al ; Dennis‐Antwi et al ; Treadwell et al ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They expressed that public education will go a long way to ameliorating public discourses around SCD as a curse or punishment and allow for conventional medical management of SCD while allowing individuals to practice their faith to cope with the complications of the disease. Previous researchers have cited the importance of embedding SCD public health and health education interventions within faith‐based communities (Anie et al ; Dennis‐Antwi et al ; Treadwell et al ).…”
Section: Discussionmentioning
confidence: 99%
“…With a broader knowledge base, religious leaders might be persuaded to take a less directive approach to counseling, leaving counseling about informed reproductive decision‐making to healthcare providers. Healthcare providers themselves in Ghana have lacked adequate knowledge and training in nondirective counseling about SCD and sickle cell trait, but we were able to expand their understanding and awareness of these techniques with our short course for nurses and health educators—Genetic Education and Counseling for Sickle Cell Conditions in Ghana (GENECIS‐Ghana; (Anie et al )). We found that participants embraced this education, recognizing the importance of empowering individuals and couples to weigh options and make informed decisions that they deem appropriate for themselves or their families.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sickle cell anemia (SCA) has been acknowledged to have a global public health impact (1) by the World Health Organization and United Nations. Over 300,000 babies are born worldwide annually with the Hb SS type of sickle cell disease (SCD) mostly in low-and middle-income countries (2) . This is considered the most prevalent hereditary chronic disease in Brazil (3) , where its distribution is quite heterogeneous, being more prevalent in the North and Northeast regions, ranging from 6% to 10%, due to a higher number of African descendants, whereas in the South and Southeast regions the prevalence is lower, from 2% to 6% (4) .…”
Section: Introductionmentioning
confidence: 99%